Modeling continuous area location monostatic doppler lidar determining wind parameters - D. V. Vasil'ev; A. I. Laryushin (Известия высших учебных заведений: Проблемы энергетики)
The application of semiconductor light sources with a spectral width of tens of kilohertz in the art of continuous Doppler lidar. The influence of the source characteristics of the formation of the zone location. To take into account the design parameters of a semiconductor source and sensitive area photodetector probe and reference channels are represented as lidar imaging system of extended coherent sources. Building location area is regarded as the imposition formed taking into account the size of the radiating surface of the source and the receiver of the sensitive area of the transverse channel image field. The proposed calculation method based on the expression of the principle of Huygens - Fresnel for long coherent sources, allows to take into account the characteristics of the emission spectrum of the optical system, the atmosphere, the size of the flat radiating surface of the source and receiver sensitive area. Results location area calculation method are confirmed by field experiments determining air flow parameters.